Animal and vegetable fats and oils. Determination of fatty-acid-bound chloropropanediols (MCPDs) and glycidol by GC/MS. Method using fast alkaline transesterification and measurement for 2-MCPD, 3-MCPD and glycidol by GC-MS/MS Part 4, (19th August 2021) - British Standards Institution,
No abstract available